2018
DOI: 10.1073/pnas.1719491115
|View full text |Cite
|
Sign up to set email alerts
|

AtPep3 is a hormone-like peptide that plays a role in the salinity stress tolerance of plants

Abstract: Peptides encoded by small coding genes play an important role in plant development, acting in a similar manner as phytohormones. Few hormone-like peptides, however, have been shown to play a role in abiotic stress tolerance. In the current study, 17 genes coding for small peptides were found to be up-regulated in response to salinity stress. To identify peptides leading salinity stress tolerance, we generated transgenic plants overexpressing these small coding genes and assessed survivability and root growth u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 60 publications
0
85
1
1
Order By: Relevance
“…PEPR1 recognizes all Pep peptides while PEPR2 recognizes only Pep1 and Pep2 (Krol et al, 2010;Bartels et al, 2013). Although it was previously described that PEPR1, but not PEPR2, is required for Pep3-triggered salt tolerance (Nakaminami et al, 2018), our analysis showed that Pep1-triggered salt tolerance was retained in pepr1 or pepr2 but abolished in pepr1 pepr2 plants ( Figures 1A, 1C, Table 1). This indicates that PEPR1 and PEPR2 both mediate salt tolerance, despite their differences in Pep ligand specificity.…”
Section: Results (24 021 Characters Excluding Figure Legends)contrasting
confidence: 49%
See 1 more Smart Citation
“…PEPR1 recognizes all Pep peptides while PEPR2 recognizes only Pep1 and Pep2 (Krol et al, 2010;Bartels et al, 2013). Although it was previously described that PEPR1, but not PEPR2, is required for Pep3-triggered salt tolerance (Nakaminami et al, 2018), our analysis showed that Pep1-triggered salt tolerance was retained in pepr1 or pepr2 but abolished in pepr1 pepr2 plants ( Figures 1A, 1C, Table 1). This indicates that PEPR1 and PEPR2 both mediate salt tolerance, despite their differences in Pep ligand specificity.…”
Section: Results (24 021 Characters Excluding Figure Legends)contrasting
confidence: 49%
“…These studies suggest that CERK1 has a role in promoting salt stress tolerance, and that this function is related to an as-yetunidentified endogenous DAMP(s). Likewise, PROPEP3 overexpression and Pep3 application under sterile conditions both enhance salt tolerance through PEPR1 (Nakaminami et al, 2018). These studies suggest that DAMP sensing and signaling contribute to salt stress tolerance, yet the underling mechanisms are not defined.…”
Section: Pti Activation Involves the Transcriptional Reprogramming Ofmentioning
confidence: 94%
“…SSPs have emerged as an important class of regulatory molecules involved in plant growth, development, plant-microbe interactions, and stress tolerance (Czyzewicz et al, 2013, Nakaminami et al, 2018, Takahashi et al, 2018. This is of particular significance for legumes, since recent discoveries show that SSPs regulate symbiotic root nodulation (Djordjevic et al, 2015, Nishida et al, 2018, Kereszt et al, 2018, and root development (Araya et al, 2016, Patel et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Small secreted peptides (SSPs) encoded in plant genomes, also termed peptide hormones, possess crucial roles in plant growth and development (Breiden & Simon 2016;Murphy, Smith, & De Smet, 2012;Patel et al, 2018). Plant SSPs have also been shown to be important regulators of stress tolerance (Nakaminami et al, 2018;Takahashi et al, 2018) and nutrient acquisition (Grillet, Lan, Li, Mokkapati, & Schmidt, 2018;Tabata et al, 2014). In light of their diverse and powerful effects on plant development and stress physiology, SSPs are of great interest for fundamental plant biology and may hold potential for yield improvements in agriculture.…”
Section: Introductionmentioning
confidence: 99%